Glacier Physics of the Puget Lobe, Southwest Cordilleran Ice Sheet - Booth, Derek (Géographie physique et Quaternaire, 1991)
ABSTRACTThe Puget lobe, the southwest-most extension of the Cordilleran ice sheet, provides an excellent opportunity to examine the connection between glacier physics and the resulting products of glaciation. The action of water, at and within the sediments of the glacier bed, is particularly significant for the geologic record of this ice sheet. Physical data and inferred mass balance relationships constrain lobe reconstruction and predict sliding velocities in excess of 500 m/a and water discharges of nearly 1 * 10" m3/a. This sub-glacial water produced a dendritic channel pattern well predicted by static analysis of sub-glacial hydrology. Near to the eastern ice margin, a much larger single channel drained subglacially and episodically, with tributary ice-dammed lakes releasing their water as jokulhlaups. Basal meltwater generated near-hydrostatic water pressures and very low till strengths at the base of the ice sheet. Water pressure dropped only close to the ice margin, allowing normal stresses to rise to significant fractions of the total ice overburden. Thus marginal and interior zones impose contrasting bed conditions. Although observation of sub-glacial deposits will reflect the late-stage passage of the marginal zone, conditions within the ice-sheet interior, far more significant to glacier history and behavior, may be substantially different.